Recurrent strokes in arterial hypertension patients (Nal’chik City Stroke Registry data) - E. S. Ulimbasheva; Yu. Ya. Varakin; S. M. Chudopal (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study arterial hypertension (AH) features in patients with recurrent stroke. Material and methods. The population method of stroke registry (two-year follow-up (2003-2004) in the city with population of 245 000) was used. In total, 1018 stroke patients were identified, including 863 primary strokes and 155 recurrent strokes. Results. Stroke incidence was 2,07 per 1000 per year: 1,76 for primary stroke, 0,31 for recurrent stroke; mortality - 1,08 per 1000 per year. Twenty-eight-day lethality was 31,7%, reaching 52,2% at one year. AH was diagnosed in 70% of stroke patients. In recurrent stroke individuals, AH was more prevalent, with higher blood pressure (BP) levels and hypertensive cerebral crises (HCC) rates. Pre-stroke BP increase was associated with stroke severity and functional recovery. In hypertensive stroke survivors, only 47% were treated regularly. Current smoking and alcohol abuse rates were 29% and 30%, respectively. Conclusion. In stroke patients, AH was diagnosed twice as often as in general population, was characterized by higher BP levels and HCC rates. Less than one half of stroke survivors received antihypertensive medications regularly.